Active Cancelling System for Mitigating ELFM Field in a High Tech Fab. (July 2020) - Lin, H Y; Chang, L M
Abstract: As nano-level of semiconductor manufacturing technology continuously advances, the demands of the high performance microscopes (HPM) and other precision instruments are increasing. To employ these microscopes and instruments, the processes involved are often venerable to electromagnetic interference (EMI), especially, the processes would be sensitively impacted by the extremely low frequency magnetic (ELFM) field. The frequency ranges of the ELFM field are from 1Hz to 3KHz. The high-intensity of ELFM field would cause measurement errors of high-precision instruments and drop production yield rate. In this paper, an active magnetic interference cancelling system (AMICS) with square Helmholtz coil structure will be utilized. The square Helmholtz coil structure is used for generating a magnetic field for mitigating the ELFM. To achieve the fast response of AMICS in regard to the ELFM field change, an embedded system with the real-time operating system (RTOS) was built to perform the magnetic measurement and magnetic cancelling task. The experimental results of research show that the ELF field cancelling capability has been improved about 95.87% for 60Hz and 96.05% for 100Hz.